Kemampuan Representasi Siswa SMP dalam The 5E Learning Cycle dengan Reflective Self Assessment pada Materi Kalor - Ida Dwi Lestari; Lia Yuliati; Hadi Suwono (Graduate School of Universitas Negeri Malang, 2018)
The 5E Learning Cycle is a constructivist learning model that can make students’ able to do competencies that must be achieved so as to increase concept mastery. The concept mastery cannot be separated from the students ability in representing material or concept that has been obtained. The representational skill helps the student in understanding the concept. The students’ representational skill is seen through self-assessment development done in each stage of learning. This research is to know the improvement of student representational skill in the 5E learning cycle with reflective self assessment. The subjects of this study were students of class VII which consits of 20 students’ in the academic year 2016/2017. The data collected in the form of test results representational skill. The instrument used is a written test amounting to 6 items of description. Quantitative data analysis used paired sample t-test, effect size, and normalized gain score. Data were analyzed qualitatively by data reduction, encoding, data presentation, and conclusion. The results showed that students' representational skill including verbal representation skill, picture and math improved after the students followed the learning using the 5E learning cycle with reflective self assessment.The 5E Learning Cycle merupakan model pembelajaran konstruktivis yang dapat membuat peserta didik menguasai kompetensi-kompetensi yang harus dicapai sehingga meningkatkan penguasaan konsep. Penguasaan konsep tidak terlepas dari kemampuan siswa dalam merepresentasikan materi atau konsep yang telah diperolehnya. Kemampuan representasi membantu siswa dalam memahami konsep. Kemampuan representasi siswa dilihat perkembangannya melalui penilaian diri yang dilakukan dalam tiap tahap pembelajaran. Penelitian ini untuk mengetahui peningkatan kemampuan representasi siswa dalam The 5E Learning Cycle dengan reflective self assessment. Subjek penelitian ini adalah siswa kelas VII yang berjumlah 20 orang pada tahun pelajaran 2016/2017. Data yang dikumpulkan berupa hasil tes kemampuan representasi. Instrumen yang digunakan adalah tes tertulis berjumlah enam butir soal uraian. Analisis data secara kuantitatif menggunakan uji paired sample t-test, effect size, dan normalized gain score. Data dianalisis secara kualitatif dengan reduksi data, pengodean, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kemampuan representasi siswa yang meliputi kemampuan representasi verbal, gambar dan matematika mengalami peningkatan setelah siswa mengikuti pembelajaran menggunakan The 5E Learning Cycle dengan reflective self assessment.